An optimised method for the rapid analysis of condensed phosphates in fishery and processed marine food products using ion chromatography and microwave sample processing. Issue 2 (1st February 2020) - Kim, Hyung Soo; Koo, Ye Ji; Lee, Miri; Pack, Eun Chul; Jang, Dae Yong; Lee, Seung Ha; Lim, Kyung Min; Choi, Dal Woong
ABSTRACT: Condensed phosphates are deliberately added to the fishery and processed marine food products on purpose to increase the weight of products. However, excessive intake overwhelming bodily homoeostasis can result in phosphate toxicity such as mineral and bone disorders, associated with chronic kidney diseases, and cardiovascular events. Rapid analysis for condensed phosphates is required to detect the illegal adulteration of processed marine products. We optimised an analytical method using ion chromatography for the rapid and selective detection of condensed phosphates in various kinds of fishery and processed marine products. We compared the performance of three columns (IonPac AS11, AS11-HC, and AS16) for the detection of condensed phosphates with respect to time of analysis and sensitivity. The IonPac AS11 column exhibited the shortest retention time for the major condensed phosphates (pyro-, tri-, and trimetaphosphate), the highest sensitivity for trimetaphosphate, and good repeatability and precision. Microwave and boiling processing were examined as methods to prevent hydrolysis of condensed phosphates into orthophosphate, which is critical in distinguishing intentionally added condensed phosphates from naturally occurring orthophosphate. Microwave treatment was determined to be the more effective method to suppress hydrolysis of condensed phosphates to orthophosphate. Furthermore, microwave processing could be used for thawing the frozen samples, saving extra effort and time. We confirmed that the method exhibits good recovery (80% or more) and precision (%RSD < 10%) for samples with various matrices. With the method, 14 kinds of fishery and processed marine food products were successfully analysed for condensed phosphates. Especially, we identified that phosphate levels in the processed shrimp and dried shredded squid samples exceeded the maximum allowable levels specified in the CODEX standard. We believe that our method would be useful for the rapid analysis of condensed phosphates in various types of fishery and processed marine food products. Graphical Abstract: